Peran Orang Tua dalam Meningkatkan Motivasi Belajar Peserta Didik di Tingkat Sekolah Dasar - Ayu, Citra; Faizah, Fitrotul; Sukmawati, Sinta (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research is based on the learning outcomes of students who are not motivated to learn by his master. This is because some parents think that the task of Motivating learning is only done by the teacher, when in fact the role of Parents are also very important. Students who do not get the motivation to learn from their parents tend to be more passive when learning, sometimes their learning outcomes are not achieve the minimum completeness criteria (KKM). With this we do a research to analyze the role of parents in increasing participants' learning motivation educated at the elementary school level. This research uses descriptive qualitative method with data collection through literature study that we have done. Writing purpose this journal so that readers know how important the role of parents in increase students' learning motivation. The results of this study that students those who get motivation to learn from their parents have better learning outcomes than students who do not get motivation to learn from their parents